The effect of organizational culture and work motivation on performance employees with organizational commitment as intervening variables (Study at the Merauke Regency DPRD Office, Mappi Regency, Asmat Regency, Boven Digoel Regency) - Layan, A. Isaak R. J.; Erari, Anita; Handoyo, Sarwo Edy (Technium Business and Management, 2024)
This study aims to determine the effect of organizational culture and work motivation on the performance of secretariat employees of the Regional House of Representatives with organizational commitment as an intervening variable in Merauke Regency, Mappi Regency, Asmat Regency, Boven Digoel Regency. The population in this study were 233 regional secretariat employees and by using purposive sampling, 106 respondents were determined. The results showed that organizational culture had a positive and insignificant effect on employee performance. Organizational culture has a positive and significant effect on employee commitment. Work commitment mediates the relationship between the influence of organizational culture on employee performance. Motivation has a positive and significant effect on employee performance. Motivation has a positive and insignificant effect on employee commitment. Work commitment does not mediate the relationship of the influence of motivation on employee performance. Organizational commitment has a negative and insignificant effect on the performance of the secretariat employees of the People's Representative Council of Merauke, Boven Digoel, Mappi, and Asmat Districts.